High throughput discovery of thermo-responsive materials using water contact angle measurements and time-of-flight secondary ion mass spectrometry - Hook, Andrew L (Blackwell Publishing Ltd, 2013)
Switchable materials that alter their chemical or physical properties in response to external stimuli allow for temporal control of material-biological interactions, thus, are of interest for many biomaterial applications. Our interest is the discovery of new materials suitable to the specific requirements of certain biological systems. A high throughput methodology has been developed to screen a library of polymers for thermo-responsiveness, which has resulted in the identification of novel switchable materials. To elucidate the mechanism by which the materials switch, time-of-flight secondary ion mass spectrometry has been employed to analyse the top 2 nm of the polymer samples at different temperatures. The surface enrichment of certain molecular fragments has been identified by time-of-flight secondary ion mass spectrometry analysis at different temperatures, suggesting an altered molecular conformation. In one example, a switch between an extended and collapsed conformation is inferred. Copyright © 2012 John Wiley & Sons, Ltd.